The effects of hydration status and ice-water dousing on physiological and performance indices during a simulated soccer match in the heat. Issue 8 (August 2021) - Benjamin, Courteney L.; Sekiguchi, Yasuki; Morrissey, Margaret C.; Butler, Cody R.; Filep, Erica M.; Stearns, Rebecca L.; Casa, Douglas J.
Abstract: Objectives: To assess the effects of hydration status and ice-water dousing on physiological and performance parameters. Design: Randomized, crossover. Methods: Twelve athletes (mean[M] ± standard deviation[SD]; age, 20 ± 1 years; height, 174 ± 8 cm; body mass, 72.1 ± 11.0 kg; VO2max 53.9 ± 7.3 mL⋅kg −1 ⋅min −1 ) completed four trials (euhydrated without dousing, hypohydrated without dousing, euhydrated with dousing, and hypohydrated with dousing), which involved intermittent treadmill running (five 15-minute bouts) in the heat (M ± SD; ambient temperature, 34.7 ± 2.1 °C; relative humidity, 46 ± 3%; wet-bulb globe temperature, 28.0 ± 0.4 °C). Participants also completed four cognitive, power, agility, reaction time, and repeated sprint performance tests throughout each trial. Heart rate (HR) and rectal temperature (Trec ) were measured continuously. Repeated measures ANOVAs were performed to assess differences between physiological and performance variables. Alpha was set at ≤0.05, a priori. Data are reported as mean difference ± standard error (MD ± SE). Results: HR was significantly lower in euhydrated trials compared to hypohydrated trials, irrespective of dousing (8 ± 2 bpm; p  = 0.001). Dousing did not significantly impact HR ( p  = 0.455) and there was no interaction between hydration and dousing ( p  = 0.893). Trec was significantly lower in euhydrated trials compared to hypohydrated trials (0.39 ± 0.05 °C, p  < 0.001), with no effect from dousing alone ( p  = 0.113) or the interaction of hydration and dousing ( p  = 0.848). Dousing resulted in improved sprint performance (11 ± 3 belt rotations, p  = 0.007), while hydration status did not ( p  = 0.235). Conclusions: Athletes should aim to maintain euhydration during exercise in the heat for improved physiological function and cooling with ice-water dousing elicits additional performance benefits.